Factors contributing to road accidents: case study of Jalan Seremban - Tampin / Nur Amalia Zulaikha ... [et al.] - Bahari, Nur Amalia Zulaikha; Mohd Nusa, Fatin Najwa; Tarudin, Nur Farizan; Mohamad, Nur Dalila; Md Murozi, Ainatul-Fatima (Universiti Teknologi MARA, 2023)
Malaysia is ranked 18th in the world for the number of people killed in road accidents. Road safety in rural areas has been less emphasized and overlooked by relevant authorities. Rembau, Negeri Sembilan is a rural area with a high road accident rate. Accidents in rural areas need urgent road safety measures to reduce road accident cases in the future. Hence, this study comprises two objectives, 1) to identify the factors contributing to road accidents at Jalan Seremban-Tampin, 2) to determine the mean rank of an accident during day and night, and to recommend common road safety approaches to reduce road accidents at the prone location. Based on the secondary accident data obtained from IPD, Rembau can find common road safety approaches worldwide to reduce road accidents at prone locations. The analysis method used was descriptive and inferential analysis, that is, Mann Whitney U using SPSS. This study revealed that human factors such as risky driver behaviour are the main factors contributing to road accidents, followed by environment or road factors. Different road safety approaches in other countries worldwide are classified into three themes, namely (i) the traditional approach, (ii) the systematic approach, and the vision-zero approach, which can be used to reduce road accidents. Therefore, this study highlights that the choice and implementation of road safety approaches varies according to each country's principles, priorities, and infrastructure based on the Sustainable Development Goal (SDG), such as targets 11.2 and 3.6.